OVERCOMING PSYCHOLOGICAL BARRIERS IN ADULT ENGLISH LANGUAGE LEARNING - Sattarova Dildora Ikramboyevna,; Jahongirova Saida Jahongir qizi, (TADQIQOTLAR, 2026)
Abstract   This  article  explores  the  psychological  barriers  that  adult  learners  face  in acquiring English language skills. It delves into common challenges such as fear of failure, lack of confidence, and anxiety, which can hinder progress and motivation. The article emphasizes the importance of understanding these barriers to create supportive learning environments. Strategies for overcoming these obstacles include fostering a growth mindset, building a sense of community among learners, and utilizing positive reinforcement techniques. By addressing psychological factors, educators can enhance the  effectiveness  of  English  language  instruction  for  adults,  ultimately  leading  to improved learning outcomes and greater learner satisfaction.